Stresses and Displacements Analyses around Tunnel Opening Under Water Body Using Finite Element Method (FEM) in Baghdad City/Middle of Iraq - Abdullah , Hamed H.; Al-Saffar, Ameer H.; Jasim, Raed S. (Iraqi Journal of Science, 2022)
In this study, the stresses and displacement around a tunnel opening under water body in Baghdad city, middle of Iraq, during excavation and lining are discussed. For this purpose, the finite element method (FEM) was adopted as an effective approach to analyze the problem using (SIGMA/W) program. The research includes the study of the behavior of soil due to excavation of a tunnel by calculating the displacements and stresses in three positions of the tunnel (crown, wall, and invert) during the various stages of construction. The surface settlement is also studied. The finite element analyses were carried out Using (Elastic- plastic) and (linear elastic) models for the soil and the concrete liner respectively.